Collaborative Governance Strategy In Sustainable Tourism Development - Ringa, Maria B.; Sahetapi, Stella Y.; Poeh, Melda M.; Kefi, Darwin Y.; Pattiasina, Victor (Public Policy, 2023)
This study aims to discover collaborative governance in managing sustainable tourism in Bajawa. This study uses phenomenology to find meaning that explores quantitative and qualitative research data. This research focuses on government collaboration divided into three processes: Dynamics of collaboration, collaborative actions, and their impact on tourism development. Data collection techniques are interviews, observations, and documentation to the government and tourism actors in 6 (six) sub-districts in Bajawa - Ngada, East Nusa